Applying Project-Based Learning to Enhance Students' English Public Speaking Skills at MTs YMPI Rappang - Aulia Pramudita Amalia; Sam Hermansyah; Andi Sadapotto; Syahrir L (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Speaking skills are a fundamental aspect of learning English as a foreign language, essential for academic and professional success. However, many students, especially in non-English-speaking environments, face difficulties in communication due to limited vocabulary, low confidence, and lack of practical speaking opportunities. This study explores the effectiveness of Project-Based Learning (PBL) in enhancing students’ English-speaking abilities at MTs YMPI Rappang. Using a qualitative case study approach, data were collected through classroom observations, interviews with teachers and students, and an analysis of students’ speaking performance before and after PBL implementation. The results show that PBL significantly improved students’ speaking skills in terms of fluency, pronunciation, grammar, and confidence. Students became more motivated to speak and actively participated in classroom discussions and group projects. The collaborative nature of PBL fostered peer learning and provided students with authentic speaking experiences, enabling them to practice English in real-world contexts. This study highlights the potential of PBL as an effective method for improving speaking skills and recommends its broader application in language teaching to create more engaging and meaningful learning experiences.